Geochemical analysis of bitumen from West Asian torpedo jars from the c. 8th century Phanom-Surin shipwreck in Thailand. (May 2020) - Connan, Jacques; Priestman, Seth; Vosmer, Tom; Komoot, Abhirada; Tofighian, Hossein; Ghorbani, Buyuk; Engel, Michael H.; Zumberge, Alex; van de Velde, Thomas
Abstract: Organic samples obtained from the interior of fragments of five different torpedo jar vessels found onboard the c . 8th century Phanom-Surin shipwreck (Thailand) were selected for geochemical analyses in order to identify the source of the bitumen lining. These samples were compared to bitumen analysed from torpedo jars excavated from various sites in the Persian Gulf and western Indian Ocean: Shaghab, Siniz, Mahroyan, Siraf, Rig Port along the coast of Iran, Sir Bani Yas in Abu Dhabi (UAE) and Anuradhapura in Sri Lanka. The geochemical data comprising biomarker and carbon isotopes on chromatographic fractions were compared to oil seep references from different areas in southern and southwest Iran. To complete the investigation, data on bitumen from several archaeological sites in Iran were used as proxies. Results show that there are two types of Iranian bitumen in the Phanom-Surin samples as well as two distinct varieties of torpedo jars. A potentially older category, represented in the assemblage by a single example, may have been kept in circulation for half a century or more beyond its period of regular use. Our results also indicate that there may be a direct correlation between the different categories of torpedo jar and the respective source of the bitumen. This study documents the links that exist between central Iraq/southwest Iran and Thailand during the 8th century AD. Highlights: Organic samples of torpedo jars from the c.8th century Phanom-Surin shipwreck were analyzed. A direct correlation exists between the different categories of torpedo jars and the respective source of the Iranian bitumen.